Verkeerde tijd, verkeerde plaats: ontmoetingen met vluchtelingen - Demyttenaere, Bart; Hannes, Nick; Tielemans, Dieter (Antwerpen: Roularta Books, 2005)
"Bart Demyttenaere ; foto's door Nick Hannes, Dieter Telemans"